Development of creative thinking in children - Moxinur Djalolova; Sherali Omonov (International Consortium of Education and Culture Research Studies, 2019)
In the article, it is stated that the development of children's creative thinking is a requirement of time, and responsibility is given to educators and psychologists employed at educational institutions, and new approaches are needed to develop creative thinking in young people.